2000
DOI: 10.1074/jbc.m008065200
|View full text |Cite
|
Sign up to set email alerts
|

Novel Catalytic Mechanism of Nucleophilic Substitution by Asparagine Residue Involving Cyanoalanine Intermediate Revealed by Mass Spectrometric Monitoring of an Enzyme Reaction

Abstract: . This enzyme has also been utilized as an industrial biocatalyst for the synthesis of chiral compounds based on its stereospecificity (2). We have studied intensely the reaction mechanism and structure of L-DEX YL, and revealed that the reaction begins with nucleophilic attack of Asp 10 on the ␣-carbon atom of L-2-haloalkanoates, causing the release of a halide ion and the formation of an ester intermediate (Scheme 1, I), which is subsequently hydrolyzed (3, 4). In the x-ray structure, there is a water molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…With the improvements of resolving power, sensitivity, and versatility, mass spectrometry has become a highly competitive analytical method for detection and characterization of biochemical reaction intermediates that can be used to elucidate enzymatic reaction pathways and catalytic mechanisms [16 -22]. Esaki et al reported a novel catalytic mechanism for L-2-Haloacid dehalogenase involving a cyanoalanine intermediate revealed by LC/MS monitoring of the enzymatic reaction [16]. Likewise, Leary and coworkers reported the identification of a sulfated NodH sulfotransferase (NodST) intermediate formed in a hybrid Ping-Pong mechanism using Fourier transform ion cyclotron resonance (FT-ICR) mass spectrometry [17].…”
mentioning
confidence: 99%
“…With the improvements of resolving power, sensitivity, and versatility, mass spectrometry has become a highly competitive analytical method for detection and characterization of biochemical reaction intermediates that can be used to elucidate enzymatic reaction pathways and catalytic mechanisms [16 -22]. Esaki et al reported a novel catalytic mechanism for L-2-Haloacid dehalogenase involving a cyanoalanine intermediate revealed by LC/MS monitoring of the enzymatic reaction [16]. Likewise, Leary and coworkers reported the identification of a sulfated NodH sulfotransferase (NodST) intermediate formed in a hybrid Ping-Pong mechanism using Fourier transform ion cyclotron resonance (FT-ICR) mass spectrometry [17].…”
mentioning
confidence: 99%
“…Curiously mutation of Rtt109p Asp-287 and Asp-288 to alanine causes a significantly greater loss of catalytic activity than the corresponding asparagine mutants (45). As the asparagine residues are unlikely to function as catalytic bases, this may reflect the fact that post-translational conversion of asparagine to aspartic acid can occur in some proteins (55)(56)(57)(58).…”
Section: Discussionmentioning
confidence: 99%
“…YL (L-DEX YL) is one of the best studied enzymes of the HAD superfamily. 6,[9][10][11][12][13][14][15][16][17][18][19][20][21][22] Mass spectrometry has played an important role in analyzing the reaction mechanism of L-DEX YL.…”
Section: L-2-haloacid Dehalogenase: a Representative Enzyme Of Thementioning
confidence: 99%
“…2). 20,21) Upon incubation with the substrate L-2-chloropropionate, the peak corresponding to the native enzyme disappeared, and a new peak appeared at 26,255 Da (M þ 73), which is considered to be an ester intermediate. These results not only verified the validity of the proposed mechanism for L-DEX YL (Fig.…”
Section: L-2-haloacid Dehalogenase: a Representative Enzyme Of Thementioning
confidence: 99%